A temática LGBTQIA+ como estratégia discursiva na comunicação da Avon Brasil - Freire, Gustavo David Araujo (2022)
Diversity is an emblem of contemporaneity triggered by movements driven, considerably, by capitalism, the market and globalization, whose reflexes are for the construction of modern identities. In the midst of this, the issue of discourse produced by organizations around the issue of sexual diversity and gender identity and expression is highlighted, as a result of a market trend that finds in social communication systems the means to establish processes of global communication. This work aims to investigate the LGBTQIA+ theme as a discursive strategy in Avon Brasil's communication, constituting a single case study. French-oriented Discourse Analysis (AD) is used as a methodological basis, aiming to give the due reflective and scrutiny treatment to the text and context, based on the use of several sources of evidence that integrate the research corpus: advertising; comments on Avon Brasil's Facebook page; sales catalogues; interviews, and; institutional documents/information. The result is the construction of a discourse that breaks with reductionist stereotypes about LGBTQIA+ people by highlighting individual freedom and empowerment. Considering its business and the target audience due to the teleological nature of the company, Avon Brasil's discursive strategies aim to explore the female universe, reflecting on the invisibility of the trans agenda regarding the figure of man (or masculine). It is worth noting that, given the strategies envisioned, the communication products do not circulate in the same way in the brand's media spaces, so that the LGBTQIA+ theme has its most significant representations on social networking sites, while, in the sales catalogs, there is not even representation, even if it is the same campaign.